LEAFLET ANATOMY OF ZAMIA DISODON D.W. STEV. & SABATO AND Z. RESTREPOI (D.W. STEV.) A. LINDSTR. - Acuña Castillo Rafael; Marín Méndez Walter (Caldasia)
The genus Zamia is morphologically and ecologically the most diverse of the Cycadales. Colombia is the country where most living species of Zamia have been recorded. Even though in the past this genus extended beyond the Neotropical region, nowadays it is almost entirely restricted to that biogeographical realm. As with the remaining Cycadales, this genus shows several unusual anatomical traits in the leaflets. The objective of this research was to study and compare the leaflet anatomy of Zamia disodon and Z. restrepoi and establish possible relationships between the anatomical traits and the habitats of these species. We found that both species share several unusual traits with each other and with other species of the genus, such as the parenchyma morphology, the distribution of tissues between the veins and the stomata morphology. The main differences between these species were seen in their fiber clusters and in the distribution and abundance of the photosynthetic tissue near the vein areas. The presence of stomata both adaxially and abaxially could be the result of the very wet habitats where both species are native, while the presence of fiber clusters just at the vein areas could account for the longevity of the leaves of Zamia. On the other hand the unique traits of Zamia restrepoi are related to the presence of a midvein, a trait not found in any other species of Zamia.